The study on structure and electrochemical sodiation of one-dimensional nanocrystalline TiO2@C nanofiber composites. (10th September 2015) - Ge, Yeqian; Zhu, Jiadeng; Lu, Yao; Chen, Chen; Qiu, Yiping; Zhang, Xiangwu
Highlights: Novel one-dimensional TiO2 @CNF composites were used as anode in sodium-ion batteries. TiO2 nanocrystals were uniformly embeded in the carbon nanofiber composites. Effects of anatase and rutile TiO2 phases on the performance of TiO2 @CNF were studied. Good cycling and rate performance of TiO2 @CNF composites were obtained. Abstract: Titanium dioxide (TiO2 ) is a prospective anode candidate for sodium-ion batteries, owing to the advantages of good chemical stability, elemental abundance and nontoxicity. In this work, TiO2 embedded in carbon nanofiber (TiO2 @CNF) composites are prepared for high-performance sodium-ion batteries by electrospinning and subsequent heat treatment in N2 at different temperatures. With increase in heat-treatment temperature, the diameter of nanofibers decreases and the crystal phase partially transforms from anatase to rutile. Among all composites, the TiO2 @CNF composite treated at 550 °C has anatase structure and exhibits the highest initial reversible capacity (237.3 mAh g −1 ), largest initial coulombic efficiency (68.2%), and superior capacity retention (100.3%) over 100 cycles at 30 mA g −1 . Whereas, the TiO2 @CNF composite treated at 650 °C is 28.23% rutile and 71.77% anatase, and shows the best rate capability of 159.1 mAh g −1 even at current density of 800 mA g −1 . It is, therefore, demonstrated that TiO2 @CNF composites prepared with appropriate conditions are superior anode material for sodium-ion batteries.